Pengembangan Buku Kendali Kedisiplinan Berbasis Nilai Karakter Islami Untuk Siswa Sekolah Dasar - Fitriani; Susi Herawati; Fadriati; Gustina (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to develop a Discipline Control Book Based on Islamic Character Values for elementary school students and to describe the feasibility and practicality of the resulting product. The study was motivated by the fact that violations of school rules are still found even though the applicable rules already include indicators of discipline. The research used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis (analysis of needs, student characteristics, and indicators of discipline and Islamic character values), design (designing the book format, indicators, and monitoring rubrics), development (product development and expert validation), implementation (limited testing of the control book), and evaluation (product evaluation and revision). Data were collected through observation, interviews, questionnaires, and documentation. The developed product contains discipline indicators integrated with Islamic character values, such as trustworthiness, responsibility, consistency, obedience to rules, and manners, accompanied by a monitoring column involving teachers and parents to reinforce student discipline habits. The results of the development show that the control book produced was deemed feasible by the validators and practical for use in school activities, thus having the potential to become a supporting medium for fostering discipline among elementary school students based on Islamic character.